The Art of Sustainability - Woods, Sarah (Peripeti, 2022)
As the systems thinker Fritjof Capra points out, through the course of Western history we have tended to give more attention to elements or things than to interconnections or relationships, thinking more mechanistically than holistically, asking “What is it made of?” rather than “What is the pattern?” 26. Sometimes, however, the study of patterns and relationships comes to the fore. Now, in our networked, digital world, as we wrestle with some of the 66 continuous problems that Donella Meadows and her team addressed in the classic Limits to Growth27, like climate change, global inequality and migration, is one of those times. This article shows the diverse and multi-fold advantages of using systems thinking as a methodology for working creatively with complexity. It explores the basic biological patterns that define life; the nature, patterns and effects of different forms of feedback; and how systems thinking can assist us in problem-solving, managing complexity and in understanding how creativity works. Living sustainably means living within the finite limits of our system. Understanding more about the systems we live with, whether through taking action on climate change or creating a well-functioning piece of art, helps us to live well and to create well.